Selected papers on Renaissance philosophy and on Thomas Hobbes - Schuhmann, Karl. author. aut Link
XIII, 278 p.
Keywords: -Selected papers on Renaissance philosophy and on Thomas Hobbes offers the best work in these fields by the acclaimed historian of philosophy, Karl Schuhmann (1941-2003), displaying the extraordinary range and depth of his unique scholarship, -Topics covered include Renaissance philosophy of nature; the development of the notion of time in early modern philosophy; Telesio's concept of space; Hermetic influences on Pico, Patrizi and Hobbes; Hobbes's Short Tract; Spinoza and Hobbes; Hobbes's political philosophy, -This book brings together, in chronological arrangement, twelve papers. Though these were published before in some form, several were not easily accessible so far, -All articles have been edited in accordance with the author's wishes, and incorporate his later additions and corrections.